Deskripsi Penggunaan ChatGPT pada Mahasiswa Tahun Ketiga Fakultas Keperawatan di Universitas X - Kusman Sudarja; Desy W. Margareth; Johanes P. Simanjuntak; Martina Endarrini; Cendana, Wiputra (Journal of Practice Learning and Educational Development, 2025)
ChatGPT is one of the Artificial Intelligence (AI) released by the American artificial intelligence research laboratory. The use of ChatGPT has various impacts on its users, both negative and positive impacts on moral and psychological aspects. Knowing the description of the use of ChatGPT in Third Year Students of the Faculty of Nursing at University X. This study uses quantitative methods with a cross sectional approach. The study was conducted in January-April 2024 with a sample of 176 students. The respondents in this study were third-year students of the Faculty of Nursing, University X. There were 92 out of a total of 176 respondents who often used ChatGPT while the remaining 84 did not use often, so it can be concluded that the description of ChatGPT use in third-year students of the Faculty of Nursing at University X is in the category of often. From this study, it is hoped that students can continue research on the description of ChatGPT use with different populations and methods and add variables related or influential to the use of ChatGPT.